Unveiling low-to-high-frequency data sampling caveats for aquaculture environmental monitoring and management - Sampaio, Fernanda Garcia; Araújo, Carlos A.S.; Dallago, Bruno Stéfano Lima; Stech, José Luiz; Lorenzzetti, João A.; Alcântara, Enner [UNESP]; Losekann, Marcos Eliseu; Marin, Diego Bedin; Leão, Joaquim Antônio Dionísio; Bueno, Guilherme Wolff [UNESP] (Elsevier, 2021)
Aiming at the sustainability of aquaculture production, producers should adopt tools and protocols for environmental monitoring and management of these enterprises. There are currently issues concerning the efficacy of data collection procedures and limnological sampling at low frequency, which is widely used by managers and aquaculture surveillance agencies. In this context, the present study evaluated the effectiveness of high-frequency (HF) and low-frequency (LF) limnological monitoring. For the HF, autonomous data collection platforms (ADCP) were installed in a tropical reservoir, four ADCP in areas with fish production (WFP), and one ADCP in an area free of fish production (FFP, control). For both sampling methods, the temperature (Temp), pH, dissolved oxygen (DO), turbidity (Tbt), electrical conductivity (EC), and chlorophyll-a (Chl-a) were sampled at a depth of 1.5 m from the water surface. While the HF used a multiparameter probe, recording each parameter every 10 min, the LF method consisted of monthly data acquisitions of the same settings using water sampling techniques for further measurement in the laboratory. The comparison of the sampling frequency and methods revealed different profiles for all measured parameters during the monitored period. The average values of the daily amplitude of variation differed between the two monitoring strategies for water temperature, pH, DO, Tbt, and Chl-a. Comparison of the results showed that the HF limnological monitoring allowed us to create a more accurate variation profile of the water quality variables measured. The ADCP is a useful strategy that can be used to capture the influences of fish production and to bring essential water quality changes for fish management. The evaluations with LF did not demonstrate the natural variability of the measured parameters, being an ineffective tool for environmental monitoring of fish production.
Keywords: Aquaculture management; Environmental monitoring; High-frequency monitoring; Innovation; Limnology; Technology